LABA/LAMA fixed-dose combinations versus LAMA monotherapy in the prevention of COPD exacerbations: a systematic review and meta-analysis. (July 2020) - Chen, Ching-Yi; Chen, Wang-Chun; Huang, Chi-Hsien; Hsiang, Yi-Ping; Sheu, Chau-Chyun; Chen, Yung-Che; Lin, Meng-Chih; Chu, Kuo-An; Lee, Cheng-Hung; Wei, Yu-Feng
Background: Long-acting muscarinic antagonist (LAMA) monotherapy is recommended for chronic obstructive pulmonary disease (COPD) patients with high risk of exacerbations. It is unclear whether long-acting β2-agonist (LABA)/LAMA fixed-dose combinations (FDCs) are more effective than LAMAs alone in preventing exacerbations. The aim of this study was to systematically review the literature to investigate whether LABA/LAMA FDCs are more effective than LAMA monotherapy in preventing exacerbations. Methods: We searched several databases and manufacturers' websites to identify relevant randomized clinical trials comparing LABA/LAMA FDC treatment with LAMAs alone ⩾24 weeks. Outcomes of interest were time to first exacerbation and rates of moderate to severe, severe and all exacerbations. Results: We included 10 trials in 9 articles from 2013 to 2018 with a total of 19, 369 patients for analysis in this study. Compared with LAMA monotherapy, LABA/LAMA FDCs demonstrated similar efficacy in terms of time to first exacerbation [hazard ratio, 0.96; 95% confidence interval (CI) 0.79–1.18; p = 0.71], moderate to severe exacerbations [risk ratio (RR), 0.96; 95% CI 0.90–1.03; p = 0.28], severe exacerbations (RR, 0.92; 95% CI 0.81–1.03; p = 0.15), and a marginal superiority in terms of all exacerbations (RR, 0.92; 95% CI 0.86–1.00; p = 0.04). The incidence of all exacerbation events was lower in the LABA/LAMA FDC group for the COPD patients with a history of previous exacerbations and those with a longer treatment period (52–64 weeks). Conclusion: This study provides evidence that LABA/LAMA FDCs are marginally superior in the prevention of all exacerbations compared with LAMA monotherapy in patients with COPD. The reviews of this paper are available via the supplemental material section.